Couple Counselling Outcomes in an Australian Not for Profit: Evidence for the Effectiveness of Couple Counselling Conducted Within Routine Practice. Issue 4 (December 2014) - Petch, Jemima; Lee, Jamie; Huntingdon, Ben; Murray, Jennifer
<x xml:space="preserve">Abstract</x> Over 30 randomised controlled trials have shown the efficacy of couple therapy under controlled conditions. However only four studies explore effectiveness of couple therapy as commonly practised in the community (i.e., routine practice). These studies suggest effectiveness is about half that reported in randomised controlled trials. Further, there are no published couple therapy effectiveness data currently from Australia or New Zealand. This is troubling because (1) couple distress has negative effects on individual adults, couples, and families; (2) funders increasingly want proof of return on financial investment; and (3) clients want hope that their emotional investment in therapy is worthwhile. The first aim of this paper is to report the outcomes of a milestone multi‐centre study of over 1, 500 Relationships Australia clients attending couple counselling. It outlines a simple, intuitive method for assessing effectiveness of couple counselling in routine practice that may motivate others to conduct effectiveness studies. The study used a cross‐sectional design and assessed current couple satisfaction and retrospective recall of couple satisfaction before attending counselling. Results revealed a moderate effect size improvement in relationship satisfaction. The results support previous published studies of couple therapy effectiveness in routine practice. The second aim of the paper is to increase interest in others doing similar research by addressing key barriers to the implementation of effectiveness studies within routine practice. These barriers include administrative burden, integration across services, and conceptual buy‐in by practitioners. The use of the retrospective measure of 'pre counselling' couple satisfaction measure overcomes these barriers in part. The paper concludes with a discussion of design limitations and suggestions for counselling agencies seeking to conduct their own effectiveness studies.